Architectural Distress: Pressure on User Comfort at The Tanjung Duren BRT Stop - Ariz Fantrio Larosa; Muhammad Siam Priyono Nugroho (Sinektika: Jurnal Arsitektur, 2026)
BRT Stops in tropical urban contexts often experience operational pressures that exceed their design capacity. This study examines architectural distress at the Tanjung Duren BRT Stop, West Jakarta, as a form of performative architectural failure. A mixed-method approach was applied, comprising spatial density analysis, circulation assessment, envelope material evaluation, thermal estimation, and user behavior observation. The findings reveal extreme crowding at 5–6 persons/m², circulation conflicts caused by a ±0.9 m bottleneck, and heat accumulation reaching approximately 51.7°C. These conditions induce psychological stress and defensive user behavior. This study conceptualizes architectural distress as a spatio-temporal, multidimensional, and replicable analytical framework for transit architecture.